How Stella learned to talk [compact disc, unabridged] : the groundbreaking story of the world's first talking dog - Hunger, Christina (Harper Audio, 2021)
An incredible, revolutionary true story and surprisingly simple guide to teaching a dog to talk from speech-language pathologist Christina Hunger, who has taught her dog, Stella, to communicate using simple paw-sized buttons associated with different words.